Cost and cost-effectiveness of PPM-DOTS for tuberculosis control: evidence from India - Katherine Floyd; VK Arora; KJR Murthy; Knut Lonnroth; Neeta Singla; Y Akbar; Matteo Zignol; Mukund Uplekar (The World Health Organization, 2006)
OBJECTIVE: To assess the cost and cost-effectiveness of the Public-Private Mix DOTS (PPM-DOTS) strategy for tuberculosis (TB) ontrol in India. METHODS: We collected data on the costs and effects of pilot PPM-DOTS projects in Delhi and Hyderabad using documentary data and interviews. The cost of PPM-DOTS was compared with public sector DOTS (i.e. DOTS delivered through public sector facilities only) and non-DOTS treatment in the private sector. Costs for 2002 in US$ were assessed for the public sector, private practitioners, and patients/attendants. Effectiveness was measured as the number of cases successfully treated. FINDINGS: The average cost per patient treated was US$ 111-123 for PPM-DOTS and public sector DOTS, and US$ 111-172 for non-DOTS treatment in the private sector. From the public sector's perspective, the cost per patient treated was lower in PPM-DOTS projects than in public sector DOTS programmes (US$ 24-33 versus US$ 63). DOTS implementation in either the public or private sectors improved treatment outcomes and substantially lowered costs incurred by patients and their attendants, compared to non-DOTS treatment in the private sector (US$ 50-60 for DOTS compared to over US$ 100 for non-DOTS). The average cost-effectiveness of PPM-DOTS and public sector DOTS was similar, at US$ 120-140 per patient successfully treated, compared to US$ 218-338 for non-DOTS private sector treatment. Incremental cost-effectiveness analysis showed that PPM-DOTS can improve effectiveness while also lowering costs. CONCLUSION: PPM-DOTS can be an affordable and cost-effective approach to improving TB control in India, and can substantially lower the economic burden of TB for patients.